Мовний образ атмосферних явищ (дощ, хмари, райдуга) в поезії Василя Голобородька - Шленьова, Марина Генадіївна (Луганський національний університет ім. Тараса Шевченка, 2014)
Статтю присвячено аналізу художньо-семантичної реалізації мовного образу атмосферних явищ (дощ, хмари, райдуга) в ідіостилі сучасного поета Донбасу Василя Голобородька. Проаналізовано формування мовного образу атмосферних явищ у поетичних текстах автора. Простежено функціонально-стильову навантаженість мовних одиниць, які є домінантними в ідіостилі письменника. Описано мовні механізми репрезентації образів дощу, райдуги та хмар у ліриці В. Голобородька. Виявлено їхню смислову багатовимірність, генетичну зумовленість ліричного функціонування з українською традиційною культурою, включеність у "резонансний простір" національної словесності. Досліджено образи дощу, хмар, райдуги в поетичних текстах Василя Голобородька на основі когнітивних механізмів, що відтворюють особливості етнічної свідомості та менталітету народу. Акцентовано на тому, що в художньому просторі митця мовний образ атмосферних явищ (дощу, хмар, райдуги) традиційно репрезентовано в тісній взаємодії з простором неба. Індивідуально-авторські порівняння й метафори віддзеркалюють розуміння письменником навколишньої дійсності, що зумовлено вживанням символічних номінацій і пошуками експресивно-емоційних еквівалентів для вираження власного ставлення до означених об'єктів.

The article devotes to the analysis of semantic realization of the atmospheric phenomena language image (rain, clouds, rainbow) in the idiostile of the modern Donbass poet Vasile Holoborodko. Necessity to outline the contours of the sky space elements which concentrate the reader’s attention, induced the author to use the art stylistic means which characterize spatial objects of the author’s language picture of the world. Formation of the atmospheric phenomena language image in poetic texts of the author is analysed. It is traced the functional and style sense of language units which are prepotent at the idiostile of the writer. Language mechanisms of representation of rain, rainbow and clouds images in V. Holoborodko’s lyrics are described. Their semantic multidimensionality, genetic conditionality of lyrical functioning with the Ukrainian traditional culture, the inclusiveness in "resonant space" of national literature are found out. Images of rain, clouds, rainbows in Vasile Holoborodko’s poetic texts on the basis of cognitive mechanisms which reproduce features of the ethnic consciousness and mentality of the people are investigated. It is accented that in Vasile Holoborodko’s art space the atmospheric phenomena language images (rain, clouds, rainbow) are traditionally represented in close interaction with sky space. Individually author's comparisons and metaphors reflect understanding of surrounding reality by the writer which is caused by the use of the symbolical nominations and searches of expressive way emotional equivalents for own relation expression to the noted objects. The conclusion is made that the most widespread art means characterizing the atmospheric phenomena are zoo- and anthropometaphors.
Language Image of the Atmospheric Phenomena (Rain, Clouds, Rainbow) in Vasile Holoborodko’s Poetry
Keywords: мовна картина світу; мовний образ; простір; мовна площина; метафора; language picture of the world; language image; space; language plane; metaphor